2022
DOI: 10.1186/s43042-022-00219-7
|View full text |Cite
|
Sign up to set email alerts
|

In-silico characterization of phytochemicals identified from Vitex negundo (L) extract as potential therapy for Wnt-signaling proteins

Abstract: Background Colorectal cancer is the third most diagnosed disease in the world population and current chemotherapy has been used for targeting the cell proliferation and metastasizing ability of tumor cells. Potent chemotherapeutic drugs for colorectal cancer are capecitabine, fluorouracil, irinotecan, etc. which have toxic effects in normal tissues and adverse effects in multiple organs leading to major obstacles in clinical use. The aim of the study is the use of plant-derived compounds that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…During the docking process, AutoDock combines the Lamarckian genetic algorithm and empirical free energy force fields to calculate the best-bound conformations and energy of the protein-ligand interactions. 69–73 Both glg and dlg files were generated using canonical Ubuntu 18.04.6 LTS (Bionic Beaver; https://releases.ubuntu.com/bionic ) as an open-source operating system by applying the Linux kernel and based on Debian. 74…”
Section: Methodsmentioning
confidence: 99%
“…During the docking process, AutoDock combines the Lamarckian genetic algorithm and empirical free energy force fields to calculate the best-bound conformations and energy of the protein-ligand interactions. 69–73 Both glg and dlg files were generated using canonical Ubuntu 18.04.6 LTS (Bionic Beaver; https://releases.ubuntu.com/bionic ) as an open-source operating system by applying the Linux kernel and based on Debian. 74…”
Section: Methodsmentioning
confidence: 99%
“…Following the heightened need for establishment of new effective curative options, recent attention has focused on the chemoprevention impact of phytochemicals such as vegetables, fruits, and medicinal plants . Based on the previously reported scientific evidence, there is a reverse association between consumption of natural products and the risk of colorectal cancer development. , …”
Section: Introductionmentioning
confidence: 99%
“…7 Based on the previously reported scientific evidence, there is a reverse association between consumption of natural products and the risk of colorectal cancer development. 8,9 Silymarin is derived from milk thistle (Silybum marianum) and comprises a mixture of flavonolignans (silybin, silydianin, and silychristin) and flavonoids (tamoxifen and quercetin). 10 It has been reported that silymarin exerts considerable antiinflammatory, anticarcinogenic, antioxidant, and proapoptotic properties.…”
Section: ■ Introductionmentioning
confidence: 99%